Change inclusive pool drains - Praderi, Raul; Gomez Fossati, Carlos; Mazza Bruno, Milton (Cirugía del Uruguay, 1974)
Tranhepatic 4-tubes are transhepatic drainages passing through bilio-digestive anastomosis from jejunum to Witzel. Since both ends of tube are exterior it is possible to change them when they become obstructed or hardened, without re-operating patient. They are specially suitable for treatment of high biliary cancers in which recurrency and stricture following anastomosis, are· frequent. These patients are definitively intubated and drainages are changed every three to four months by painJess manouvres. 4-tubes are also absolutely indicated in treatment of sclerosing cholangitis, but not in bening stricture of biliary tract which are generally solved by Jeft transhepatic I'-tubes.